Job flow dynamics and firing restrictions: evidence from Europe - Julián Messina; Giovanna Vallanti (Institute for the Study of Labor (IZA), 2006)
We exploit homogeneous firm level data of manufacturing and non-manufacturing sectors to study the impact of firing restrictions on job flow dynamics across 14 European countries. We find that more stringent firing laws dampen the response of job destruction to the cycle, thus making job turnover less counter-cyclical. Moreover, the impact of firing costs on job creation and job destruction varies across sectors, depending on sector-specific trend growth. Our findings clearly suggest that such costs are more important in contracting than in growing sectors.
Keywords: J23; J63; J68; 330; gross job flows; Europe; business cycle; firing costs; Arbeitsmarkt; Personalabbau; Personalbedarf; Personalkosten; Konjunktur; Westeuropa